Characterization of Bioactive Compounds from Aqueous Layer of Guiera senegalensis Leaf Extract - Bilyamin Adam, Ansar; Bashir Ahmad , Kabiru; Abdulmumin muhammad, Ma'aruf; Bashir, AL Amin; Victoria Abdulmalik, Isah; Yahaya Abubakar, Musa (Al-Kimia, 2024)
There is need to have cost-effective treatment strategy by using medicinal plant that have therapeutic potentials against varieties of disease due to presence of bioactive compound. The study aimed to characterize the bioactive compounds from the aqueous layer of Guiera senegalensis leaf extracts. Aqueous layer extracts from Guiera senegalensis leaf were prepared and analyzed using FTIR and GCMS. The GCMS result of the plant extract reveals the presence of Carboxylic acid and its derivatives and other compounds such as n-Propyl 11-octadecenoate , Aspidospermidin-17-ol, 1-acetyl-19,21-epoxy-15,16-dimethoxy- . The results of the study have justified therapeutic potential of Guiera senegalensis plant extract. FTIR result indicate a signal at 3205 cm-1which is a vigorous intensity which is attributed to carboxylic acid, a strong signal was observed at 2926 cm-1which is attributed to C-H stretch (alkane),carbon-oxygen (C-O) band was observed at 1200 cm-1 which is attributed to ester, carboxylic acid or ether and aromatic functional carbon-carbon double bond at 1442 cm1, a strong intensity was observed at 1602 cm-1, which is attributed to N-H bend of primary amine, aromatic ring stretch at 1457 cm-1 was also observed with medium intensity. Alkane bend vibration was observed at 1375cm-1, and a strong signal was observed at 1162cm-1, which is attributed to C-N (Amine).